Black Skiing, Everyday Racism, and the Racial Spatiality of Whiteness. (November 2013) - Harrison, Anthony Kwame
This article examines how structural and symbolic forces combine to produce racialized discourses of belonging and geographies of exclusion in and around downhill skiing. Drawing from literatures in Whiteness studies, sports sociology, leisure studies, and environmental history, I advance the concept of racial spatiality to illustrate how processes of everyday racism work to secure skiing's social spaces as predominantly White, thereby restricting the participation and representation of Black skiers. Skiing's hegemony of Whiteness is discussed in relation to parallel integration strategies of Black ski organizations, racialized representations of extreme skiing and snowboarding, and exclusionary residential development tactics. As a provisional effort to promote research on racism and leisure–sports–tourism, I argue that skiing offers a valuable site for considering the ongoing and overlooked saliencies of race and racial segregation in America.